Perception of self-motion: Vection experiments in multi-sensory Virtual Environments - Schulte-Pelkum, J. (Ruhr-Universität Bochum, 2007)
This dissertation investigated how visual, auditory, vestibular, and somatosensory information contribute to the perception of self-motion. Utilising the versatility of modern Virtual Reality (VR) technology, multi-sensory interactions in self-motion perception that have not been investigated previously were studied. One guiding question was how these multi-sensory processes and also cognitive factors, such as spatial presence in VR, contribute to self-motion perception, and how these can be applied in order to improve self-motion simulation. Six psychophysical experiments are reported that investigated multi-sensory and cognitive aspects of the vection illusion, which is an illusion of self-motion in stationary observers. First, it was shown that the results of vection experiments using VR technology were comparable to studies that used traditional psychophysical apparati, such as optokinetic drums. Then, it was found that natural, realistic visual stimuli induce stronger vection than artificial stimuli, and also increase presence in VR. Following this, the question was asked how consistent multi-sensory information can intensify the perceived magnitude of this illusion. The interactions between visual, vestibular, auditory, and somatosensory stimuli (vibrations) during selfmotion perception were systematically studied. The main finding is that the self-motion illusion can be significantly increased by adequate multi-sensory stimulation, compared to a purely visual baseline, and that also cognitive, higher-level factors, such as spatial presence in the simulated Virtual Environment can have a significant influence on vection. Based on these results, it is discussed how perceptually optimised VR environments might improve self-motion simulation. The results of this thesis and several other recent studies in the field of self-motion perception are discussed in the context of different theoretical approaches to multi-sensory integration and self-motion perception. Finally, an integrative conceptual model about self-motion perception is proposed that incorporates the findings from the current thesis and other recent studies on this topic.
Keywords: Riecke; Riecke_2007; Riecke_seniorCoSupervised_thesis; Riecke_supervised_thesis; bernhard-riecke; joerg-schulte-pelkum; multi-modal vection; supervisedThesis; thesis; vection